2012
DOI: 10.1007/s12298-012-0125-7
|View full text |Cite
|
Sign up to set email alerts
|

A simple, novel and high efficiency sap inoculation method to screen for tobacco streak virus

Abstract: A rapid and efficient sap inoculation method for tobacco streak virus (TSV) was developed in sunflower. Sap from TSV-infected sunflower plants was freshly extracted in phosphate buffer and diluted serially from 10(-1) to 10(-8). Two-day old seedlings of sunflower were injured at the meristem and immersed in the sap for 10 min, maintained at 20 °C for 2-3 days and shifted to greenhouse. The surviving seedlings in the respective sap dilution were scored for symptoms of sunflower necrosis disease (SND). SND sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…In general, Ilarvirus has a wide host range as they are efficiently sap transmissible to many of the host plants belonging to Amaranthaceae, Chenopodiaceae, and Fabaceae. A rapid and efficient sap inoculation method for tobacco streak virus (TSV-SF) has been developed for screening a large number of sunflower geno types for resistance to the disease (Sundaresha et al 2012).…”
Section: Mechanical/sap Transmissionmentioning
confidence: 99%
“…In general, Ilarvirus has a wide host range as they are efficiently sap transmissible to many of the host plants belonging to Amaranthaceae, Chenopodiaceae, and Fabaceae. A rapid and efficient sap inoculation method for tobacco streak virus (TSV-SF) has been developed for screening a large number of sunflower geno types for resistance to the disease (Sundaresha et al 2012).…”
Section: Mechanical/sap Transmissionmentioning
confidence: 99%
“…Singh and Awasthi 33 reported different artificial mechanical transmission of virus like TMV, CMV, TSV, Okra mosaic virus, Papaya ringspot virus, Cowpea mosaic virus and alfalfa mosaic virus in tobacco, tomato, sunflower, okra, papaya, cowpea and potato (Sacrista´n et al 34 ; Jalender et al 35 ; Sundaresha et al 36 ; Givord and Hirth 37 ; Gonsalves 38 ; Surekha et al 39 ; El-Abhar et al 40 ). and wheat.…”
Section: Mechanical Transmission With Mymv Maintained Agrobacterium Clonesmentioning
confidence: 99%
“…Studies have shown that the selection of suitable plant tissues and inoculation sites is the key to successful infection. Commonly used tissues include the meristems of seedlings [ 23 ], three-week-old micro-shoots [ 24 ], and the stems or petioles of 4–6 leaf stage plants [ 25 ]. However, the use of such sites is complicated and time-consuming, increasing the operational complexity of inoculation [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used tissues include the meristems of seedlings [ 23 ], three-week-old micro-shoots [ 24 ], and the stems or petioles of 4–6 leaf stage plants [ 25 ]. However, the use of such sites is complicated and time-consuming, increasing the operational complexity of inoculation [ 23 25 ]. Therefore, a rapid, simple, economical, and highly efficient VIGS and virus inoculation method is in need.…”
Section: Introductionmentioning
confidence: 99%